Superior Customer Value: Strategies For Winning and Retaining Customers - McFarlane, Donovan A. (Indian Journal of Marketing, 2013)
Customer value has become a strategically significant factor in global competitiveness and its value as a vehicle for transitioning from market-driven and reactive to market-driving and anticipatory firms is being increasingly recognized. Dr. Art Weinstein communicates this understanding and paradigm in customer value theory and conception more effectively than any other writers, academicians, practitioners and authors. This book review examines Dr. Art Weinstein's recently published book, Superior Customer Value: Strategies for Winning and Retaining Customers (Third Edition, 2012). The reviewer explores the contents of Dr. Weinstein's book and his customer value theory by examining the major theoretical and practical frameworks and principles that affect and underscore the creation of value in today's highly competitive new economy characterized by a dominant service sector and technology-based activities and firms. This book review further explores Dr. Weinstein's rationale and wisdom for making such a poignant and devoted call to companies large and small, private and public, as well as those which are manufacturing and those which are service firms to design, implement, and deliver superior customer value not only as a quality-based competitive strategy, but simply because it is the right thing to do because customers expect only the very best from today's organizations - no less and no more. This book review explores Dr. Weinstein's philosophy that designing and delivering superior customer value is not an option in today's rapidly transforming global economy and market; it is a requirement; and one critical in determining which companies will remain market followers (market driven), which will emerge as market leaders (market driving), and which companies will simply disappear as they fail to create and deliver value that meets customers' growing and changing needs and wants. Book: Superior Customer Value: Strategies for Winning and Retaining Customers Author: Art Weinstein (2012) Publisher: CRC Press: Boca Raton, Florida, USA Edition: Third ISBN 978-1-4398-6128-8 Price: USD 69.95 Pages: 319 pages Binding: Hardcover